Unraveling the Relationship among the Kirati Languages - Rai, Tara Mani (Nepalese Linguistics, 2024)
This paper explores the relationships among the Kirati languages through lexical comparisons. The analysis, employing the Swadesh 100-word list, shows that Bantawa and Puma as well as Mugali and Phangduwali exhibit the highest lexical similarity, at 52%, while Yakkha and Koits-Sunuwar have the lowest similarity, at just 1%. In terms of phonetic similarity, Bantawa and Puma also show the greatest resemblance, with a similarity rate of up to 68%, whereas Mugali and Wambule show the least similarity, at 34%. These findings reveal that the lexical similarities and differences among the Kirati languages may reflect their geographical distribution and historicity.